2018
DOI: 10.1182/blood-2017-06-789842
|View full text |Cite
|
Sign up to set email alerts
|

Red cell exchange transfusions lower cerebral blood flow and oxygen extraction fraction in pediatric sickle cell anemia

Abstract: Blood transfusions are the mainstay of stroke prevention in pediatric sickle cell anemia (SCA), but the physiology conferring this benefit is unclear. Cerebral blood flow (CBF) and oxygen extraction fraction (OEF) are elevated in SCA, likely compensating for reduced arterial oxygen content (CaO). We hypothesized that exchange transfusions would decrease CBF and OEF by increasing CaO, thereby relieving cerebral oxygen metabolic stress. Twenty-one children with SCA receiving chronic transfusion therapy (CTT) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 64 publications
7
107
9
Order By: Relevance
“…Kuwabara et al (2002) also found that OEF changed little with decreasing [Hb] in a study of anaemic adults. This lack of a significant OEF increase in response to anemia in normocapnia contrasts to that observed in sickle cell children Guilliams et al 2018) and infants (Morris et al 2018) where OEF increases in concert with CBF in response to anemia, and may be the result of an increased CMRO 2 (Bush et al 2014), which is predicted by the model but not shown. Further, in regions of the brain such as the white matter where perfusion is poor (Mandell et al 2008), D O 2 is decreased Chai et al 2019).…”
Section: Cbf In Anaemia and Hypocapniacontrasting
confidence: 67%
“…Kuwabara et al (2002) also found that OEF changed little with decreasing [Hb] in a study of anaemic adults. This lack of a significant OEF increase in response to anemia in normocapnia contrasts to that observed in sickle cell children Guilliams et al 2018) and infants (Morris et al 2018) where OEF increases in concert with CBF in response to anemia, and may be the result of an increased CMRO 2 (Bush et al 2014), which is predicted by the model but not shown. Further, in regions of the brain such as the white matter where perfusion is poor (Mandell et al 2008), D O 2 is decreased Chai et al 2019).…”
Section: Cbf In Anaemia and Hypocapniacontrasting
confidence: 67%
“…There was no cutoff across different quantiles that predicted OS or EFS. Since the median VAF in our population (43%) was very similar to the previous cutoff reported by others to predict survival (44%), 4 we used a cutoff of 43% to correlate NPM1 VAF with outcomes. For the entire population, OS and EFS were not different between patients with VAF <43% and ≥43% ( Figure 1A,B).…”
Section: Haploidentical Bone Marrow Transplantation Improves Cerebralmentioning
confidence: 54%
“…Regional OEF methods have been applied in this population as well. 4 Our study highlights the importance of central neuroradiology adjudication of MRI and MRA of the brain 10 NPM1 mutant variant allele frequency correlates with leukemia burden but does not provide prognostic information in NPM1-mutated acute myeloid leukemia…”
Section: Haploidentical Bone Marrow Transplantation Improves Cerebralmentioning
confidence: 84%
See 2 more Smart Citations